An Increased Business Opportunity of Wellness Tourism as Premium Tourist Destination in Asian Countries - Keadplang, Kittiya (Journal of Cultural Approach, 2019)
Wellness tourism is an attractive tourism for people who are seeking for an escape because of a pressure of work and everyday life. Especially, beauty and anti–aging, spas, fitness, mind–body, healthy eating, health–orientated treatment business and etc. are Wellness tourism is an attractive tourism for people who are seeking for an escape because of a pressure of work and everyday life. Especially, beauty and anti–aging, spas, fitness, mind–body, healthy eating, health–orientated treatment business and etc. are included in the global wellness tourism industry that has gained high revenues in many countries. The trend of wellness tourism is more valuable significantly and people will travel in many Asian Countries. Therefore, the preparation of wellness tourism business plays an important role to serve the people demands. These reasons mean people have to spend a day off, holiday, vacation to restore their well–being and health by escaping away from their repeated environment and land.